Inhibition of endogenous ouabain by atrial natriuretic peptide is a guanylyl cyclase independent effect. - Gulay Tegin (Public Library of Science (PLoS), 2021)
Background Endogenous ouabain (EO) and atrial natriuretic peptide (ANP) are important in regulation of sodium and fluid balance. There is indirect evidence that ANP may be involved in the regulation of endogenous cardenolides. Methods H295R are human adrenocortical cells known to release EO. Cells were treated with ANP at physiologic concentrations or vehicle (0.1% DMSO), with or without guanylyl cyclase inhibitor 1,2,4 oxadiazolo[4,3-a]quinoxalin-1-one (ODQ). Cyclic guanosine monophosphate (cGMP), the intracellular second messenger of ANP, was measured by a chemiluminescent immunoassay and EO was measured by radioimmunoassay of C18 extracted samples. Results EO secretion is inhibited by ANP treatment, with the most prolonged inhibition (90 min vs ≤ 60 min) occurring at physiologic ANP concentrations (50 pg/mL). Inhibition of guanylyl cyclase with ODQ, also reduces EO secretion. The inhibitory effects on EO release in response to cotreatment with ANP and ODQ appeared to be additive. Conclusions ANP inhibits basal EO secretion, and it is unlikely that this is mediated through ANP-A or ANP-B receptors (the most common natriuretic peptide receptors) or their cGMP second messenger; the underlying mechanisms involved are not revealed in the current studies. The role of ANP in the control of EO synthesis and secretion in vivo requires further investigation.